Perbandingan Kinerja iOS dan HarmonyOS dalam Performances - Hidayat, Chaerul; Prasetyo, Fabian Eka; Rilvani, Elkin (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
This study compares the performance of two leading mobile operating systems, iOS and HarmonyOS, focusing on technical aspects such as power efficiency, application response speed, background application management, and graphics rendering performance. Using a literature review method, data was collected from scientific sources, comparative reports, and official documents. The analysis results show that iOS excels in hardware-software integration, providing high energy efficiency and stable performance, especially on mobile devices. In contrast, HarmonyOS stands out for its flexibility and multi-device integration, making it ideal for the IoT ecosystem. However, this flexibility has limitations on energy efficiency and performance of some devices. The study concludes that iOS is suitable for users who prioritize a stable and exclusive experience, while HarmonyOS is more ideal for those who need the flexibility of an open ecosystem.